Language and Identity: A Case Study on Queer Community Language in Dean Modah Tiktok Videos - Harijanto, Shelvie; Novaldi Gabriel Dimara, Willem (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
TikTok has been effective in cultivating a creative arena where users can easily access and make digital material by using a collection of shared audios, filters, text-to-speech, and a special system for user involvement. Digital platform such as TikTok continues to promote social conduct motivated by the need for acceptance from the community. This paper explores Queer’s English language used in Dean Modah's TikTok videos. By applying a sociolinguistic approach, this paper examines the English language used by Queer community to express their identity. The results show that the English language used by Queer community undergoes a morphological process, particularly a coinage process. The meanings of Queer language are different from the lexical meanings. The new meaning formulation denotes the dominant personal function of the language used. The new meaning formulation in Queer English language use is to support the community members to freely express themselves. It can be concluded that word formulation, changes in meaning, and use of language identify the identity of the Queer community.